2015
DOI: 10.1016/j.brat.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a brief school-based body image intervention ‘Dove Confident Me: Single Session’ when delivered by teachers and researchers: Results from a cluster randomised controlled trial

Abstract: ISRCTN16782819.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 33 publications
6
72
1
3
Order By: Relevance
“…Being the first evaluation of a social media‐literacy intervention, it is not possible to compare outcomes with similar previous research. However, small to medium effect size improvements were consistent with previous school‐based body image interventions that included media literacy material without focusing on social media (Diedrichs et al, ; Dunstan et al, ; McLean et al, ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Being the first evaluation of a social media‐literacy intervention, it is not possible to compare outcomes with similar previous research. However, small to medium effect size improvements were consistent with previous school‐based body image interventions that included media literacy material without focusing on social media (Diedrichs et al, ; Dunstan et al, ; McLean et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…Peer approaches target the peer environment and peer interactions as risk factors for body dissatisfaction and disordered eating and aim to improve the peer appearance culture and reduce pressure to adhere to appearance ideals (McLean et al, ). Randomized controlled trials of school‐based programs incorporating these components have found positive outcomes for body dissatisfaction and disordered eating (e.g., Dunstan, Paxton, and McLean, ; Diedrichs et al, ; McLean et al, ) but such approaches have not previously been evaluated in the context of social media, nor have they identified the mechanisms accounting for program effects.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this there were a number of positive post‐program outcomes for a single‐session version of Happy Being Me in a recent large‐scale evaluation ( N = 1,707), including improved body image in girls. This single‐session did also lead to an increase in awareness of sociocultural pressures for girls to be thin at post‐program, but not at 1–2‐month follow‐up, in the teacher‐led condition . The authors suggested that this effect could be due to awareness of pressures rather than resulting upset or concern.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies suggested the efficacy of prevention programs in school context and educational training focused on the increase of body esteem during this developmental age (Neumark-Sztainer, Paxton, Hannan, Haines, & Story, 2006;Duncan, Al-Nakeeb, & Nevill, 2009;Ross, Paxton, & Rodgers, 2013;Diedrichs, Atkinson, Steer, Garbett, Rumsey, & Halliwell, 2015;Halliwell, Yager, Paraskeva, Diedrichs, Smith, & White, 2016). For example, Halliwell et al (2016) carried out a study on the intervention program realized by teachers in order to improve the body satisfaction of English girls and boys of 9-10 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Ross et al (2013) found the increase of body satisfaction among primary school Australian girls (aged 11 -12 years), noticing that the intervention group took into consideration positive image of their body and positive attitudes as "thin-ideal internalization", "body comparison", and "self-esteem". Recently, Diedrichs et al (2015) tested the effectiveness of a brief school-based body image intervention (named as "Dove Confident Me:…”
Section: Introductionmentioning
confidence: 99%